Wawasan Kebangsaan Dalam Bingkai NKRI - Muhammad Idris (STAI Tebing Tinggi Deli, 2020)
Nationality or nationalism on a national scale is defending the country. Defendingthe state is not enough to foster a sense of nationality and nationalism only foryoung people, for students, for those on campus. However, a sense of nationalitymust also be instilled in state officials and apparatus.In the course of history, ideas, attitudes, and determination have arisen that arederived from the cultural values of the nation and are inspired by the noble moralideals of the people. This attitude and determination are the embodiment of anational insight.The Indonesian National Insight mandates all nations to place unity, integrity,and the interests and safety of the nation and state above personal or groupinterests. It is hoped that Indonesian people are able and willing to sacrifice forthe benefit of the nation. In this regard, respect for human dignity, love for themotherland and nation, democracy and social solidarity should be fostered.